The influence of global financial crisis on Jordanian equity market: VECM approach - Bekhet H.A.; Matar A. (Inderscience Publishers, 2023)
The current paper attempts to analyse the causality and co-integration relationship between the global financial crisis and the general stock price index (SPI) in the Jordanian equity market for the 1978-2011 period. A vector error correction model (VECM) is utilised to test the causal relationship between SPI and its determinants [gross domestic product (GDP), money supply (M2), exchange rate (EX) and consumer price index (CPI)]. The results identify a co-integration between SPI and Jordanian macroeconomic variables indicating a long-run equilibrium relationship among them. The error-correction term coefficient has a significant negative sign pointed to the adjustment back from short-run disequilibrium to the long-run equilibrium. The Granger causality test suggests a bidirectional causal relationship between SPI and M2 in the short and long runs. In addition, the results reveal that the global financial crisis has a positive significant impact on the SPI. Copyright 2013 Inderscience Enterprises Ltd.